Improving the Conventional Pelletization Process to Save Energy during Biomass Densification - Zhongjia Chen; Guosheng Yu; Xiangyue Yuan; Qingyu Wang; Jiangmin Kan (BioResources, 2015)
A pellet mill is currently the most frequently used method for producing pellets using either a ring die or a flat die. In the densification process, a great amount of energy is required to avoid spring-back and to overcome the friction between the material and the channel surface of the die. However, extra energy is unnecessarily consumed because of friction between the roller and densified material and the pressure between the roller and die, where there are no opening channels. The aim of this work was to attempt to eliminate a portion of the frictional and compaction energy consumption based on an improved method of densification using a ring die. An upgraded pellet mill was designed and manufactured with rams on its roller. When the die and the roller rotate in a fixed transmission ratio, the rams precisely press raw material into opening channels on the die. Experimental tests on its feasibility were carried out. The results showed that the pellet mill, with this improvement, worked without wear on the surface of either the ring die or the roller; furthermore, the density and mechanical durability of pellets were the same as those produced using the traditional method.